Gene expression profiles provide insights into the survival strategies in deep-sea mussel (Bathymodiolus platifrons) of different developmental stages - Junrou Huang; Peilin Huang; Jianguo Lu; Nengyou Wu; Genmei Lin; Xilin Zhang; Hong Cao; Wei Geng; Bin Zhai; Cuiling Xu; Zhilei Sun (BMC Genomics, 2022)
Abstract Background Deep-sea mussels living in the cold seeps with enormous biomass act as the primary consumers. They are well adapted to the extreme environment where light is absent, and hydrogen sulfide, methane, and other hydrocarbon-rich fluid seepage occur. Despite previous studies on diversity, role, evolution, and symbiosis, the changing adaptation patterns during different developmental stages of the deep-sea mussels remain largely unknown. Results The deep-sea mussels (Bathymodiolus platifrons) of two developmental stages were collected from the cold seep during the ocean voyage. The gills, mantles, and adductor muscles of these mussels were used for the Illumina sequencing. A total of 135 Gb data were obtained, and subsequently, 46,376 unigenes were generated using de-novo assembly strategy. According to the gene expression analysis, amounts of genes were most actively expressed in the gills, especially genes involved in environmental information processing. Genes encoding Toll-like receptors and sulfate transporters were up-regulated in gills, indicating that the gill acts as both intermedium and protective screen in the deep-sea mussel. Lysosomal enzymes and solute carrier responsible for nutrients absorption were up-regulated in the older mussel, while genes related to toxin resistance and autophagy were up-regulated in the younger one, suggesting that the older mussel might be in a vigorous stage while the younger mussel was still paying efforts in survival and adaptation. Conclusions In general, our study suggested that the adaptation capacity might be formed gradually during the development of deep-sea mussels, in which the gill and the symbionts play essential roles.